Pengaruh Stres Kerja dan Beban Kerja Terhadap Kinerja Melalui Kepuasan Kerja Sebagai Variabel Intervening pada PT Maxipro Group Indonesia - Wijayanti, Firda Nur; Iristian, Jovi; Adistie, Gisti Riza (Mabny: Journal of Sharia Management and Business, 2024)
Job stress and high workload can reduce employee performance. High job satisfaction can be a mediator that minimizes the negative impact of work stress and workload on performance. This research was conducted with the aim of determining the effect of work stress and workload on performance through job satisfaction as an intervening variable at PT Maxipro Group Indonesia. The population used in this research was all 25 employees of PT Maxipro Group Indonesia. The sampling technique uses saturated samples so that the entire population is used. The data collection technique uses a quantitative approach with a causal associative nature. The data source for this research comes from questionnaire answers which are then analyzed using path analysis with the Partial Least Square (SmartPLS) application. The research results show that work stress does not have a significant effect on job satisfaction. Workload does not have a significant effect on job satisfaction. Work stress has a significant effect on performance. Workload does not have a significant effect on performance. Job satisfaction has a significant effect on performance. There is an indirect effect which is not significant, which means that job satisfaction does not mediate the effect of work stress on performance. There is an insignificant indirect effect, which means that job satisfaction does not mediate the effect of workload on performance.